The Web-Based Birth Certificate Validity Information System for Disdukcapil Magetan Services - Liswardana Gostafi Arifin; Ervin Yohannes (Universitas Negeri Surabaya, 2026)
Abstract—Digital public services demand strict information security guarantees, particularly in the management of vital civil-registration documents such as birth certificates. This study designs and develops a web-based Birth Certificate Validity System (E-Akta) for the Population and Civil Registration Office (Disdukcapil) of Magetan Regency, replacing an unstructured WhatsApp-based workflow with an application that integrates the principles of an Information Security Management System (ISMS) based on ISO/IEC 27001. The system was built with the Django framework and emphasizes the three pillars of the CIA Triad: Confidentiality, Integrity, and Availability. A custom registration flow records applicant data, followed by mandatory core-data entry, a multi-step document-upload wizard, and a review page prior to permanent storage. The system was evaluated through Black-Box Testing of its functional modules, technical security testing of built-in Django safeguards, and a user-acceptance survey of ten respondents using a five-level Likert scale. The results show that built-in security features—CSRF protection, PBKDF2 password hashing, and server-side validation—successfully preserve data confidentiality and integrity against manipulation attempts, while a real-time status-tracking feature improves service availability for applicants and simplifies monitoring for administrators. Functional testing achieved a 100% success rate, and the user-acceptance survey produced an overall score of 92.8%, categorized as